2016
DOI: 10.1590/1981-38212016000100002
|View full text |Cite
|
Sign up to set email alerts
|

Elite Framing of Inequality in the Press: Brazil and Uruguay Compared

Abstract: Current elite studies argue that inequality produces negative externalities to elites, who may either promote democracy or adopt authoritarian measures in order to shield their interests from the actions of the rebellious poor. This article argues that elite framing of poverty and inequality in the press is a good thermometer of elite public response to such externalities. The press represents a communication tool shared by elites in the state, market, civil society, and, most evidently, the media itself. If i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Professional news media, at this point, prefer to serve as a channel of communication between party elites. This close relationship with political power means that the media frame is dominated by the views of the party elites (Lau, 2012;Lopez, 2016). In Bourdieu's theory, the media's covert use of elite opinions legitimizes its ideas.…”
Section: Dualism Of Media Faces and The Battle For Media Powermentioning
confidence: 99%
“…Professional news media, at this point, prefer to serve as a channel of communication between party elites. This close relationship with political power means that the media frame is dominated by the views of the party elites (Lau, 2012;Lopez, 2016). In Bourdieu's theory, the media's covert use of elite opinions legitimizes its ideas.…”
Section: Dualism Of Media Faces and The Battle For Media Powermentioning
confidence: 99%
“…Since democratization, Latin American elites have been challenged by unions, left-wing parties, social movements and guerrillas, while also facing extreme levels of criminal violence. Moreover, research shows that elites in the region acknowledge inequality as the cause of social conflict (López, 2013b(López, , 2016Reis & Moore, 2005). However, elites less often pursue democratic reversals.…”
Section: High Inequality and Democracymentioning
confidence: 99%
“…Elites also have reasons to feel threatened by unintended consequences of inequality. Research on elite attitudes toward inequality has found that elites associate inequality with crime and violence and perceive themselves as victimized (López, , , ; Reis, ; Reis & Moore, ). In a similar vein, elites in countries such as Brazil appear to see inequality as a threat to liberal institutions that they have learned to treasure and as fuel for political phenomena, such as left‐wing populism that they despise.…”
Section: Introductionmentioning
confidence: 99%
“…The latter cluster became known as “Bolivarian” in reference to Chavez's leitmotif of a “Bolivarian revolution,” associated with new forms of populism (Padoan, ; Roberts, ). These patterns served as examples of the “dangers” of political competition in the eyes of elites and were frequently invoked by mainstream media as rhetorical devices aimed at limiting or preventing redistributions (López, ).…”
Section: Introductionmentioning
confidence: 99%